Structural and optical analysis of Eu3+/Sm3+ co-doped zinc borosilicate glass fabricated by modified melt-quenching method - Cheong, Wei Mun; Zaid, Mohd Hafiz Mohd; Yap, Wing Fen; Tan, Sin Tee; Matori, Khamirul Amin; Loh, Zhi Wei; Ismail, Ismayadi; Schmid, Siegbert (Springer, 2023)
In this work, Eu3+/Sm3+ co-doped zinc borosilicate glass was prepared by modified melt-quenching method. The effect of Eu3+/Sm3+ to the structural and optical properties was investigated. The optical band gaps increased from 5.023 to 5.179 eV, and 3.832 to 3.986 eV for both for direct/indirect transition. Urbach energy decreases from 0.713 to 0.697 eV, while refractive index also decreases from 2.203 to 2.173 with the progress of doping concentration. The photoluminescence measurement reveals the simultaneous amplification of Sm3+ and Eu3+ emission for the co-doping sample, suggesting a synergistic energy transfer between the two ions. The 1EuSmZBS glass samples show the highest emission intensity. The CIE chromaticity coordinates, CCT, and color purity of the glass sample present high intensity of reddish-orange emission color. In conclusion, Eu3+/Sm3+ co-doped zinc borosilicate glass can lead to enhanced and tunable luminescence properties, and potentially use as a glass host phosphor in optoelectronic applications.